Qualitative alteration of peripheral motor system begins prior to appearance of typical sarcopenia syndrome in middle-aged rats - Tamaki, Tetsuro; Hirata, Maki; Uchiyama, Yoshiyasu (Frontiers in Aging Neuroscience, 2014)
Qualitative changes in the peripheral motor system were examined using Young, Adult, Middle-aged and Old-aged rats in order to assess before and after the appearance of sarcopenia symptoms. Significant loss of muscle mass and strength, and slow-type fiber grouping with a loss of innervated nerve fibers were used as typical markers of sarcopenia. Dynamic twitch and tetanus tension and evoked electromyogram (EEMG) were measured via electrical stimulation through the sciatic nerve under anesthesia using our force-distance transducer system before and after sciatectomy. Digital and analogue data sampling was performed and shortening and relaxing velocity of serial twitches was calculated with tension force. Muscle tenderness in passive stretching was also measured as stretch absorption ability, associated with histological quantitation of muscle connective tissues. The results indicated the validity of the present model, in which Old-aged rats clearly showed the typical signs of sarcopenia, specifically in the fast-type plantaris muscles, while the slow-type soleus showed relatively mild syndromes. These observations suggest the following qualitative alterations as the pathophysiological mechanism of sarcopenia: 1) reduction of shortening and relaxing velocity of twitch; 2) decline of muscle tenderness following an increase in the connective tissue component; 3) impaired recruitment of motor units (sudden depression of tetanic force and EEMG) in higher stimulation frequencies over 50-60 Hz; and 4) easy fatigability in the neuromuscular junctions. These findings are likely to be closely related to significant losses in fast-type motor units, muscle strength and contraction velocity, which could be a causative factor in falls in the elderly. Importantly, some of these symptoms began in Middle-aged rats that showed no other signs of sarcopenia. Thus, prevention should be started in middle age that could be retained relatively higher movement ability.